Housing for disabled people: what do they need? - Ab Rahman, Syakir Amir; Samsudin, Nasriah; Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (2017)
Across the world, people with disabilities, advocacy companies, key non-authorities and government stakeholders are trying to find approaches to enhance housing assist preparations for the disable people. By the year 2020, Malaysia aims to be a developed nation with high economic status. In line with that, the housing industry should become adaptive to meet the demand of the people with special needs. The government also needs to plan for suitable housing policies for all groups of people which are sustainable housing policy. House is the central focus for human being including the disabled people and houses that follow housing standard for the disabled will improve their quality of life, thus able to create stability. The price, location and design of residential property were said to be the most important factor in the selection of property purchase. Buyers typically give primary consideration to the accessibility, convenience and proximity to the property (Hamid, 2006). According to Elizabeth and Julia (2015), the universal home includes thoughtful and well-planned features that make the residence more usable by all family members. This paper aims to study the preferences in term of price, location and design factor in owning residential property among the disabled community in Kuala Lumpur and Selangor. The method used is the quantitative approach where a questionnaires survey were distributed to 400 respondents among the disabled community with mainly focused on two categories of disability, the physical and visual impairment. The outcome of this study will describe the preferences in owning residential property in term of the price, location and design of the residential property. It concludes by providing the recommendation on housing strategy in planning for the price, location and design of residential property for the disabled community in Kuala Lumpur and Selangor.